The role of clinical and anamnestic data in the primary diagnosis of genital endometrios - T. V. Skapchuk; I. V. Kalinovska (Zaporozhye State Medical University, 2024)
To date, many randomized studies have proven the importance of evaluating clinical and anamnestic data in the initial diagnosis of genital endometriosis. Clinical assessment of "classic" complaints of patients, which are characteristic of genital endometriosis, allows to predict the presence of endometriosis with a high probability, which is an important component of choosing the optimal treatment tactics. Despite a fairly significant number of developed questionnaires for the assessment of endometriosis symptoms, none of them has been widely used among domestic clinicians. Implementation of a diary of symptoms of endometriosis in practice will allow to more carefully assess the general pain of endometriosis, the impact on the patient's quality of life, and also to evaluate the quality of the chosen method of treatment. The aim of the study: on the basis of a retrospective analysis of patients' disease histories, assessment of the presence of clinical and anamnestic data characteristic of genital endometriosis in accordance with the obtained results of pathohistologically confirmed endometriosis. Materials and methods. We performed a retrospective analysis of 160 patient histories. The criteria for selecting patients with genital endometriosis were the presence of the following symptoms: premenstrual pain syndrome, dysmenorrhea, dyspareunia, the nature of menstrual discharge (brown discharge before and after menstruation), chronic pelvic pain, as well as confirmation, with the help of histopathological examination, of genital endometriosis. Results. By comparing the obtained data on pain symptoms with the clinical diagnosis made on the basis of histopathological examination, it can be concluded that the symptoms were most likely caused by endometriosis. Conclusions. Clinical and anamnestic data most characteristic of genital endometriosis were found in 138 (86.25 %) patients, data on the frequency of combination of painful symptoms were as follows: combination of two symptoms in 27.50 % (n = 44), three symptoms in 26.88 % (n = 43), four symptoms in 14.38 % (n = 23) and five studied symptoms in 6.25 % (n = 10), which in turn influenced the choice of the expected volume of surgical intervention and contributed to the establishment of a clinical diagnosis. The description of pain symptoms is quite limited, since the assessment of the characteristic symptoms of genital endometriosis did not include: conducting additional examinations in order to exclude additional causes of functional pain in the pelvis, the description of pain symptoms was incomplete, which, in turn, minimized the assessment of the adverse impact on daily activities, work or the quality of life in general, characteristic of pain symptoms, there is no clear difference between chronic pelvic pain and dysmenorrhea, the absence of data regarding the work of the gastrointestinal tract and urinary system, regarding the symptoms of genital endometriosis, which may indicate damage to the above-mentioned departments.